2015
DOI: 10.5350/dajpn2015280205
|View full text |Cite
|
Sign up to set email alerts
|

The impact of caregivers’ expressed emotion and the patients’ perception of expressed emotion on the positive and negative symptoms of patients with schizophrenia in a sample from Turkey

Abstract: The impact of caregivers' expressed emotion and the patients' perception of expressed emotion on the positive and negative symptoms of patients with schizophrenia in a sample from TurkeyObjective: Although the effects of caregivers' expressed emotion on the relapse of patients with schizophrenia have been studied widely, there is a relative paucity of research on how the patients' perceived expressed emotion affects outcome in schizophrenia. The main aim of this study was to examine the relative impacts of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Bu durum, destekleyici aile ortamının şizofreni hastalarında depreşmelere karşı koruyucu bir faktör olması nedeniyle önemli bulunmuştur. [42] Bireyleri aileleriyle birlikte ele alan çalışmaların uygun baş etme yöntemleri geliştirmede etkili olacağı düşünülmektedir.…”
Section: Katılımcıların Taburculuk Sonrası Bakım Gereksinimleriunclassified
“…Bu durum, destekleyici aile ortamının şizofreni hastalarında depreşmelere karşı koruyucu bir faktör olması nedeniyle önemli bulunmuştur. [42] Bireyleri aileleriyle birlikte ele alan çalışmaların uygun baş etme yöntemleri geliştirmede etkili olacağı düşünülmektedir.…”
Section: Katılımcıların Taburculuk Sonrası Bakım Gereksinimleriunclassified
“…Moreover, family’s importance increased with the community-based approach (Chan, 2010). Also in Turkey, most people with schizophrenia live with their families (Bastug & Karanci, 2015; Karanci & İnandılar, 2002) and de-institutionalization was started in recent years. The number of Community Mental Health Centers (CMHCs) starts increasing as well.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the concept of caregiving burnout was initially applicable to professional roles, modern day research has aptly disclosed that family members and relatives of individuals with mental disorders tend to suffer from burnout symptoms comparable to the symptoms experienced by professionals, including psychiatrists and nurses [22,23]. The feeling of emotional exhaustion and drain does not only proffer adverse effect on the family and relative's quality of life and is regarded as a risk to the relative's and family's mental problems, but additionally prompts negative defense mechanisms that adversely impact their involvement in the provision of care to the patient [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, recent studies have indicated that significant correlations exist between relatives and families of the patients and the patient's mental disorders. For instances, a recent study by Bastug disclosed that bipolar disorder patient's relatives and family are likely to experience less burnout compared to the other mental disorder patients' families, as well as that, in instances where the mental illness began two or more years earlier, the family members and relatives were highly prone to suffer increased degrees of burnout or subjective burden [24]. Such observations may be interpreted to imply that it is appropriate for support groups to be offered to divergent categories of families and relatives of the psychiatric patients based on the type of mental disorder, an aspect that has never been applied in practice [31].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%